Prokaryotic Collagen-Like Proteins as Novel Biomaterials - Picker, Jonathan; Lan, Ziyang; Arora, Srishtee; Green, Mykel; Hahn, Mariah; Cosgriff-Hernandez, Elizabeth; Hook, Magnus (Frontiers in Bioengineering and Biotechnology, 2022)
Collagens are the major structural component in animal extracellular matrices and are critical signaling molecules in various cell-matrix interactions. Its unique triple helical structure is enabled by tripeptide Gly-X-Y repeats. Understanding of sequence requirements for animal-derived collagen led to the discovery of prokaryotic collagen-like protein in the early 2000s. These prokaryotic collagen-like proteins are structurally similar to animal collagens in many ways. However, unlike the challenges associated with recombinant expression of mammalian collagens, these prokaryotic collagen-like proteins can be readily expressed in E. coli and are amenable to genetic modification. In this review article, we will first discuss the properties of mammalian collagen and provide a comparative analysis of mammalian collagen and prokaryotic collagen-like proteins. We will then review the use of prokaryotic collagen-like proteins to both study the biology of conventional collagen and develop a new biomaterial platform. Finally, we will describe the application of Scl2 protein, a streptococcal collagen-like protein, in thromboresistant coating for cardiovascular devices, scaffolds for bone regeneration, chronic wound dressing and matrices for cartilage regeneration.